Five-year experience of anorectal malformation with oesophageal atresia in tertiary care hospital - Sarita Chowdhary; Pranay Panigrahi; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2020)
Aim: We had done this study for TEF with Anorectal malformation and TEF with no Anorectal malformation in terms of age, sex, surgical outcomes and mortality. Materials and Methods: This was a retrospective review of cases with clinical data (from April 2012 to April 2017). The participants of this study were 236 patients who had been diagnosed and managed for ARM. Among these patients, 25 patients associated with EA were selected as the subject patient group. Results: The incidence of tracheoesophageal fistula with ARM was 11.1%. The study has more male preponderance. All cases are of Type c except two cases of Type a. According to the classifications of ARMs, there were two cases with rectourethral fistula and eight cases with rectoperineal fistula and covered anus in the males. In females, there was a varied distribution of seven cases. There was one case (4%) presenting as a part of the Vertebral anorectal malformation cardiac tracheoesophageal renal and limb anomalies (VACTERL) association, which is the representative example of a complex anomaly. Most of the cases died due to cardiac problem and pneumonitis (due to delayed presentation). Conclusion: The study concludes the experience of EA (±fistulae) with ARM, their distribution, incidence and outcome of the tertiary care centre.